A Corpus-Based Approach to Clause Combining in English from the Systemic Functional Perspective - He, Qingshun (The M.A.K. Halliday Library Functional Linguistics Series, 2019)
This book presents corpus-based research on functional syntax. It is the first book to present a comprehensive investigation into grammatical metaphor in English clause combining in large-size corpora. By providing a systematic illustration of features such as parataxis, hypotaxis and embedding, it fills a gap in the systemic functional literature. It also offers insights into testing grammatical metaphors using a corpus linguistics methodology. The book is a useful resource for anyone interested in writing development. .